Effectiveness of medicinal leech therapy on infected postauricular ulcer: a case report - Ramakrishnan, Sinjid; Bhandari, Madan; B. J., Gopikrishna; K. R., Sahanasheela (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Trauma induced auricular partial defect very common. Due to the aesthetic value, proper reconstruction has to be done preserving the symmetry of bilateral auricles. The reconstruction of auricle is difficult due to the intricate anatomy of the auricle, limited and inconsistent vascularization and the high ratio of cartilage to skin. Historically, Susruta was the first author to describe about auricular repair. In Ayurveda, medicinal leech therapy is praised for it’s usefulness for the healing of ulcers. In this case report, a male of 30 years with a trauma induced postauricular infected ulcer was successfully treated with the application of medicinal leeches for multiple sittings.